Pressure pain sensitivity as a marker for stress and pressure pain sensitivity-guided stress management in women with primary breast cancer. (August 2014) - Axelsson, Christen K.; Ballegaard, Søren; Karpatschof, Benny; Schousen, Peer
Abstract Objectives. To validate (1) Pressure Pain Sensitivity (PPS) as a marker for stress and (2) a PPS-guided intervention in women with primary Breast Cancer (BC). Methods. (1) A total of 58 women with BC were examined before and after 6 months of intervention. A control group of 165 women office employees was divided in a High Stress Group (HSG, n = 37) and a Low Stress Group (LSG, n = 128) to evaluate the association between PPS, questionnaire-related Quality of Life (QOL) and self-evaluated stress. (2) A PPS-guided stress management program (n = 40) was compared to a Psychosocial Group Intervention (PGI, n = 91) and no treatment (n = 86) with respect to a European Organization for Research and Treatment of Cancer (EORTC) questionnaire measured QOL. Results. (1) Resting PPS and changes in PPS during the intervention period correlated significantly to EORTC and Short Form 36 (SF 36) main scores: (all p < 0.05). Between BC, HSG and LSG there was a significant and positive correlation with respect to PPS, SF 36 main scores, depression, and clinical stress scores (all p < 0.05). However, the BC group scored significantly lower than both HSG and LSG (both p < 0.05) with respect to self-evaluated stress. (2) The PPS-guided intervention group improved EORTC main score, pain and nausea, when compared to the control groups (all p < 0.05). Conclusions. PPS was positively associated with QOL, which was in contrast to self-evaluated stress. PPS-guided intervention improved QOL in women with breast cancer.